Investigation of the Asymptotic Behavior of Generalized Baskakov-Durrmeyer-Stancu Type Operators - Torun, Gülten; Mercan Boyraz, Meliha; Dinlemez Kantar, Ülkü (Cumhuriyet University, 2022)
In this manuscript, we firstly find the Korovkin test functions for the Baskakov operators, secondly, we find the generalized Baskakov-Durrmeyer-Stancu type operators. Thirdly, we give the modulus of continuity for the generalized Baskakov-Durrmeyer-Stancu type operators. Then, the asymptotic approach of these operators has been studied by using the Voronovskaja-type theorem. Finally, it is demonstrated that the generalized Baskakov-Durrmeyer-Stancu type operators converge to the considered function by plotting the graphs. Moreover, the convergence of the generalized Baskakov-Durrmeyer-Stancu type operators is compared with that of some other operators to the same function.
Keywords: Matematik; Voronovskaja type theorem; Voronovskaja type theorem; Baskakov operators; Mathematical Sciences